Real-time RT-PCR for Venezuelan equine encephalitis complex, Madariaga and Eastern equine encephalitis viruses: application in human and mosquito public health surveillance in Panama - Carrera,J-P; Araúz,D; Rojas,A; Cardozo,F; Stittleburg,V; Morales,Claro I; Galue,J; Lezcano-Coba,C; Romero,Rebello Moreira F; -Rivera,LF; Chen-Germán,M; Moreno,B; et al. (Journal of Clinical Microbiology, 2023)
Eastern equine encephalitis virus (EEEV), Madariaga virus (MADV), and Venezuelan equine encephalitis virus complex (VEEV) are New World alphaviruses transmitted by mosquitoes. They cause febrile and sometimes severe neurological disease in human and equine hosts.Detecting them during the acute phase is hindered by nonspecific symptoms and limiteddiagnostic tools. We designed and clinically assessed reverse transcription polymerase chain reaction assays (rRT-PCRs) for VEEV complex, MADV, and EEEV using whole-genome sequences. Validation involved 15 retrospective serum samples from 2015-2017 outbreaks, 150 mosquito pools from 2015, and 118 prospective samples from 2021-2022 surveillance in Panama. The rRT-PCRs detected VEEV complex RNA in 10 samples (66.7%) from outbreaks, with one having both VEEV complex and MADV RNAs. VEEV complex RNA was found in 5 suspected dengue cases from disease surveillance. The rRT-PCR assays identified VEEV complex RNA in 3 Culex (Melanoconion) vomerifer pools, leading to VEEV isolates in 2. Phylogenetic analysis revealed the VEEV ID subtype in positive samples. Notably, 11.9% of dengue-like disease patients showed VEEV infections. Together, our rRT-PCR validation in human and mosquito samples suggests this method can be incorporated into mosquito and human encephalitic alphavirus surveillance programs in endemic regions.